2021
DOI: 10.1002/tox.23439
|View full text |Cite
|
Sign up to set email alerts
|

miR‐141‐3p regulates saturated fatty acid‐induced cardiomyocyte apoptosis through Notch1/PTEN/AKT pathway via targeting PSEN1

Abstract: It has been reported that miR-141-3p levels are markedly upregulated in the cardiomyocytes of obese rats induced by a high-fat diet. However, the role of miR-141-3p in myocardial lipotoxicity remains elusive. In the present study, the role of miR-141-3p in lipotoxic injury of H9c2 cells induced by palmitic acid (PA) and its possible mechanisms were assessed. The results indicated that miR-141-3p was significantly upregulated in PA-induced cardiomyocytes. miR-141-3p inhibitor enhanced the cell viability, reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…miR-141-3p has recently emerged as a key regulator required in the CNS for multiple biological functions, 20 and miR-141-3p serves dual functions in apoptosis and autophagy. 11 , 13 , 15 , 16 However, no previous studies have investigated the effects of miR-141-3p on apoptosis and autophagy in rat fetuses with ARMs. The current findings demonstrate a critical role for miR-141-3p in maintaining homeostasis in the central nervous system of defecation and reveal that miR-141-3p overexpression in ARMs triggered apoptosis and repressed autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-141-3p has recently emerged as a key regulator required in the CNS for multiple biological functions, 20 and miR-141-3p serves dual functions in apoptosis and autophagy. 11 , 13 , 15 , 16 However, no previous studies have investigated the effects of miR-141-3p on apoptosis and autophagy in rat fetuses with ARMs. The current findings demonstrate a critical role for miR-141-3p in maintaining homeostasis in the central nervous system of defecation and reveal that miR-141-3p overexpression in ARMs triggered apoptosis and repressed autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…miR-141-3p upregulation in decidual natural killer cells could be associated with unexplained recurrent spontaneous abortions, 10 and an miR-141-3p inhibitor decreased apoptosis and repressed activation of the mitochondrial apoptosis pathway in palmitic acid-treated H9c2 cells. 11 miR-141-3p overexpression significantly suppressed ectopic endometrial stromal cell proliferation, while promoting apoptosis. 12 Conversely, it is also reported that miR-141-3p inhibition induced apoptosis, suppressed proliferation, and reduced profibrotic markers in hepatic stellate cells by blocking the PTEN-AKT pathway.…”
Section: Introductionmentioning
confidence: 89%